National Trends of Vascular Risk Factor Control Among Stroke Survivors in Korea: From the National Health and Nutrition Examination Survey 2010 to 2021 - Lee, Eung-Joon; Jeong, Han-Yeong; Jung, Keun-Hwa (Journal of Korean medical science, 2025)
To prevent stroke recurrence in stroke survivors, effective management of vascular risk factors (VRFs), including hypertension, diabetes, hyperlipidemia, and smoking, is essential. This study aimed to assess the VRF control status and trends among stroke survivors in Korea. This cross-sectional study analyzed data from 1,261 stroke survivors aged ≥ 19 years (mean age: 65.2 years; 43.1% female) who were part of the Korea National Health and Nutrition Examination Survey from 2010 to 2021. The control status of VRFs was evaluated using standardized criteria: hypertension (blood pressure < 140/90 mmHg), diabetes (hemoglobin A1c < 7%), hyperlipidemia (low-density lipoprotein cholesterol [LDL-C] < 70 mg/dL), and smoking status. Multivariate logistic regression analysis was conducted to identify factors associated with uncontrolled VRFs. The rates of age-adjusted hypertension, diabetes, and smoking control remained consistent throughout the observation period. However, overall LDL-C control improved from 30.1% in 2010-2012 to 40.4% in 2019-2021 ( = 0.015), particularly in those aged ≥ 65 years. However, in the 19-49 age group, the control rate decreased from 47.0% to 15.8% ( = 0.048). Smoking rates showed no significant improvement (70.2% in 2019-2021 compared to 69.6% in 2010-2012), particularly among men. Living alone (adjusted odds ratio [aOR], 1.85; 95% confidence interval [CI], 1.03-3.32) was significantly associated with uncontrolled hypertension, whereas living in urban areas was linked to uncontrolled diabetes (aOR, 2.75; 95% CI, 1.06-7.17). Non-health screening was significantly associated with uncontrolled hyperlipidemia (aOR, 2.28; 95% CI, 1.25-4.14), and men were more likely to continue smoking (aOR, 4.47; 95% CI, 3.12-6.72). These findings highlight the need for targeted health strategies to enhance risk-factor management and reduce stroke recurrence.